Will I Cooperate? The Moderating Role of Informational Distance on Justice Reasoning - Melkonian, Tessa (Journal of business ethics, 2016)
This study examines the influence of a dimension of a strategic organizational change context—namely informational distance—on employees’ justice expectations and their behavioral intentions toward the change. Drawing on research from organizational justice and from construal level theory, we hypothesize that informational distance, i.e., the extent to which employees feel knowledgeable about the coming change, affects the relative influence of the anticipatory justice facets and anticipatory overall justice in predicting support for change. Consistent with the hypotheses, results from participants of a merger suggest that when employees feel less knowledgeable about the future change (high-informational distance), overall anticipatory justice predicts their intention to cooperate with the change. However, when employees feel more knowledgeable about the future change (low-informational distance), anticipatory justice facets predict intention to cooperate. Implications for research on organizational justice and change as well as considerations for practice are discussed.